Carbono acumulado en la biomasa vegetal de la reserva de Villavicencio (Mendoza-Argentina) - Zivkovic, Liliana (2013)
Carbon storage in the plant biomass of the Villavicencio Nature Reserve (MendozaArgentina). Nature reserves play a relevant role in carbon storage in arid lands. The vegetation of the Nature Reserve of Villavicencio stores 98798 Mg (2.1 Mg/ha) of carbon in total; considering the Puna and unburned Monte vegetation, 91.2% of carbon occurs in aboveground parts (leaves and stems) and 8.8% in the root system. Monte vegetation, characterized by Larrea cuneifolia shrubland, stores 77905 Mg C (3.9 Mg/ha), 78.8% of the total carbon in the area. Nanophanerophytes store 28.8% in the unburned shrubland, and 50.4% in the area burned in 2000, while chamaephytes store 95.5% in the area burned in 2005. In the Puna belt, with 20893 Mg C (0.78 Mg/ha) stored, Jarava vaginata grassland dominates and stores 88% of carbon, aboveground parts (leaves of grasses and leaves and stems of chamaephytes) store 90% of carbon. In general, and taking into account both vegetation belts, 19.8% of the carbon present in the Reserve is stored in nanophanerophytes, 32.8% in hemicryptophytes, 28.8% in chamaephytes and 18.4% in succulents (cactaceae). Assessment of carbon storage, taking into account the different phytogeographic units, is necessary for management of the protected area and for a better understanding of the role of these environments in the mitigation of atmospheric carbon.